W poszukiwaniu telewizyjnego newsa - Mielczarek, Remigiusz (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2013)
The author is a reporter on local television; he describes the nature of his work based on his own experience. He proposes a definition of news, describes its informational role, and explains both how to search for information and how to edit it. He also gives examples of well-known journalism authorities in Lodz.